Identification of leptin gene polymorphisms associated with carcass traits and fatty acid composition in Japanese Black cattle. (18th July 2016) - Kawaguchi, Fuki; Okura, Kazuki; Oyama, Kenji; Mannen, Hideyuki; Sasazaki, Shinji
Abstract: Previous studies have indicated that some leptin gene polymorphisms were associated with economically important traits in cattle breeds. However, polymorphisms in the leptin gene have not been reported thus far in Japanese Black cattle. Here, we aimed to identify the leptin gene polymorphisms which are associated with carcass traits and fatty acid composition in Japanese Black cattle. We sequenced the full‐length coding sequence of leptin gene for eight Japanese Black cattle. Sequence comparison revealed eight single nucleotide polymorphisms (SNPs). Three of these were predicted to cause amino acid substitutions: Y7F, R25C and A80V. Then, we genotyped these SNPs in two populations (JB1 with 560 animals and JB2 with 450 animals) and investigated the effects on the traits. Y7F in JB1 and A80V in JB2 were excluded from statistical analysis because the minor allele frequencies were low (< 0.1). Association analysis revealed that Y7F had a significant effect on the dressed carcass weight in JB2; R25C had a significant effect on C18:0 and C14:1 in JB1 and JB2, respectively; and A80V had a significant effect on C16:0, C16:1, C18:1, monounsaturated fatty acid and saturated fatty acid in JB1. The results suggested that these SNPs could be used as an effective marker for the improvement of Japanese Black cattle.